(untitled) (Circe de clásicos y modernos, 2021)
In this article we look into two tragedies in which the concepts of libido and luxus play an important role within the tragic representation: Phaedra and Thyestes show on stage two different representations of luxury, each driven by a particular kind of libido, which may seem to go along the usual admonitory and moral representation of Seneca’s time. But these tragedies go a little bit further, because by presenting rhetorically on stage the paupertas and also a return to a Natural state, they actually deconstruct the idea of Nature by presenting it as an artifice.